Learning Strategies Of Sunday School Teachers In Installing The Character Of Discipline - Romika, Romika; Sianturi , Ruth (CV. AFDIFAL MAJU BERKAH, 2024)
Sunday School means traditional church To train children in Biblical truth. However, Sunday Schools, and more broadly, children's ministry programs, are undergoing a change in identity. The aim of this research is to describe Sunday school teachers' strategies in instilling disciplined character in GBI Bassura Sunday School children. The method used in this research is a qualitative descriptive method with a literature review approach, which means through a study of various references. The research results show that Sunday School teachers should develop learning strategies that contain a disciplinary character. Possible strategies include: 1) Developing a learning curriculum based on discipline education, 2) Conducting regular meetings between parents and Sunday School children, 3) Determining punishments and rewards, 4) Carrying out group coaching, 5) Implementing habituation methods. In conclusion, by consistently implementing effective strategies, the Sunday Teachers' School will give birth to a generation of Christians who have disciplined character in accordance with Christian values.